Development of Moke Local Context Based Audio Visual Learning Media on Addictive Substances - Laudasarni, Yohana; Kua, Maria Yuliana; Suparmi, Ni Wayan; Dinatha, Ngurah Mahendra (SEARCH: Science Education Research Journal, 2026)
This study aimed to develop audio visual learning media on addictive substances based on the local context of moke in Ngada Regency. The development was motivated by the limited use of contextual learning media in science instruction, particularly those integrating local cultural contexts relevant to students’ daily lives. This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through observations, expert validation sheets, and teacher and student response questionnaires. Data were analyzed descriptively using quantitative methods. The results showed that the developed media obtained an average validity score of 3.75, categorized as very valid. In addition, the practicality level reached 94.47% based on student responses and 90.90% based on teacher responses, both categorized as very practical. These findings indicate that the developed audio visual learning media is feasible and practical for use in junior high school science learning. The integration of moke local context in the media provides a contextual learning resource that may support students’ understanding of addictive substances in relation to their surrounding environment.